2023
DOI: 10.1021/acs.jpcb.2c08485
|View full text |Cite
|
Sign up to set email alerts
|

Critical Beginnings: Selective Tuning of Solubility and Structural Accuracy of Newly Synthesized Proteins by the Hsp70 Chaperone System

Abstract: Proteins are particularly prone to aggregation immediately after release from the ribosome, and it is therefore important to elucidate the role of chaperones during these key steps of protein life. The Hsp70 and trigger factor (TF) chaperone systems interact with nascent proteins during biogenesis and immediately post-translationally. It is unclear, however, whether these chaperones can prevent formation of soluble and insoluble aggregates. Here, we address this question by monitoring the solubility and struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…These proteins include dihydrofolate reductase (DHFR), λ-lysozyme, green fluorescent protein, firefly luciferase, , tailspike, and several others . Additional recent work on apoMb revealed that the ribosome has a nascent chain solubilizing character. , The above results show that the ribosome has a remarkable ability to support the solubility and folding of a variety of proteins even in the complete absence of external molecular chaperones. The findings presented above, in combination with the research presented here, suggest a link between the nonpolar character of the newly discovered L23 interaction site and the known nascent chain solubilizing action of the ribosome.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…These proteins include dihydrofolate reductase (DHFR), λ-lysozyme, green fluorescent protein, firefly luciferase, , tailspike, and several others . Additional recent work on apoMb revealed that the ribosome has a nascent chain solubilizing character. , The above results show that the ribosome has a remarkable ability to support the solubility and folding of a variety of proteins even in the complete absence of external molecular chaperones. The findings presented above, in combination with the research presented here, suggest a link between the nonpolar character of the newly discovered L23 interaction site and the known nascent chain solubilizing action of the ribosome.…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, translation outcomes of wild-type apoMb are very similar in the absence and presence of TF, with the only detectable difference being the presence of ca. 30% fewer soluble aggregates when TF is present . Previous studies showed that the interaction of full-length nascent E. coli globin domains with ribosomal proteins are mostly displaced by interactions with TF at physiologically relevant TF concentrations (ca.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations